Dino Buzzati in Albania - Teneqexhi, Alba (Richtmann Publishing, 2012)
â€œMagical realismâ€ flourished in the literature of 1979-1980 through books and translations from the foreign writers. One of themost well-known writers of this trend was the italian writer Dino Buzzati. This paper aims to present works and books of Albaniantranslators such as Dritan and Zija Cela, Hasan Bregu, Mimoza Hysa, etc who have embraced the works of Dino Buzzati. The focus ofthe study is the work â€œSixty narrativesâ€ whose stories will be approached and compared to the works of Albanian writers. This study willpoint out translation as a difficulty and barrier of reading and understanding. The structure of Buzzatiâ€™s short stories is extremely uniqueand special. He manages to relate the real world with the imaginary one in his own way. Words and language are of the mediumregister, not elaborated and syntax is developed in a different way. This study helps the field of literature translation through acomparative method. Expected results: Albanian translators have coped with the difficulties of translation and have achieved to presentthe original work of the italian writer Dino Buzzati